Entre a cruz e a espada : contornos da Justiça Restaurativa mobilizada pela Pastoral Carcerária - Machado, Amanda Castro (2023)
This dissertation studies the contours of Restorative Justice applied by Pastoral Carcerária (PCr), verifying if restorative theories and practices are aligned with a Latin American emancipatory strand of Restorative Justice or if it is possible to identify punitive traits that distance it from a libertarian line. Furthermore, it investigates whether any punitive traits would be caused by the PCr's Catholic origin or not. This investigation was carried out through the study of the historical-theoretical frameworks "Theology of Liberation", "history of the Brazilian Pastoral Carcerária", "emancipatory Latin American Restorative Justice (JRELA)" and "structural violence". Since this is an empirical qualitative research, semi-structured interviews were conducted with pastoral agents who occupy the position of RJ teachers in the PCr and/or supervisors of restorative practices at the PCr and, once these data were collected, the analysis of the oral texts was carried out using methodological tools of French Semiotics. Still, three surveys conducted by PCr itself on projects involving RJ were also examined. In the end, it is concluded that the RJ applied by the PCr, as well as its body of pastoral agents, can be considered heterogeneous, neither absolutely restorative nor fully punitive, but rather with traces of both rationalities, and directed to the JRELA in terms of the intention of the interlocutors and the National PCr.